Comparative Efficacy of Phaseolus aureus Extract and Synthetic Growth Regulators on Callus Induction in Curcuma xanthorrhiza - Faramayuda, Fahrauk; Melani, Putri Dwi; Elfahmi, Elfahmi (AGROSCRIPT: Journal of Applied Agricultural Sciences, 2025)
Temulawak (Curcuma xanthorrhiza Roxb) a plant indigenous to Indonesia, is increasingly recognized for its medicinal properties, formulating a cornerstone of traditional medicine with annual usage marking a significant growth rate of approximately 5.4%. As awareness of its therapeutic potential expands, too does the demand for this valuable resource, necessitating enhanced efforts in its propagation and the extraction of its bioactive compounds. This study investigates the efficacy of different growth regulators in the induction of callus tissue from C. xanthorrhiza through plant tissue culture, a key method for regenerating valuable plant material. Specifically, the research focuses on the comparative effects of natural growth regulators, particularly water extracts from Phaseolus aureus, and synthetic growth regulators such as 2,4-Dichlorophenoxyacetic Acid (2,4-D) and Indole-3-butyric Acid (IBA) in varied concentrations. The experimental design included varying concentrations of P. aureus water extract at 10%, and 15%, alongside a fixed concentration of the synthetic agents. Findings indicated that synthetic growth regulators, particularly the combination of 2,4-D and IBA at a concentration of 0.4 ppm each, yielded superior callus proliferation compared to the natural extract treatments. However, P. aureus aqueous extract showed positive effects also on callus emergence and on increasing explant size when used at 10% concentration in Murashige-Skoog medium. Consequently, the study underscores the potential of integrating both natural and synthetic growth regulators to enhance callus induction and ultimately facilitate the sustainable use of C. xanthorrhiza as a medicinal resource.